I need it for home work and i need help please its hard

J=Justin's money; A=Ava's; E=Emma's.

J=A+7.5; E=J-12; A+E+J=63. So A=J-7.5. Now we have E and A in terms of J.

Substitute for A and E: J-7.5+J-12+J=63; 3J-19.5=63, 3J=63+19.5=82.5, so J=82.5/3=27.5 or \$27.50.

So A=27.5-7.5=\$20; E=27.5-12=\$15.50.

CHECK: Justin has \$7.50 more than Ava. True. Emma has \$12 less than Justin. True. Together they have \$63. True.
by Top Rated User (884k points)
Let's keep it a problem with one variable

Since Justin has 7.50\$ more than Eva, and Emma has 12\$ less than justin then we will have:

Eva has X dollars, and justin must have X+7.50\$ then Emma should have X+7.50\$ -12\$ =X - 4.50\$

The total is 63\$ therefore  (Eva's  X  + Justin's  X + 7.50\$  + Emma's X - 4.50\$) = 63

X + X + 7.50 + X - 4.50 = 63 therefore 3X + 3 = 63 let's divide everything by three to simplify 3X/3 + 3/3 = 63/3

X + 1 = 21  therefore  X = 21 - 1 = 20  Eva has 20\$,  Justin has 20\$ + 7.50\$= 27.50\$ and Emma has 27.50\$ - 12\$ = 15.50\$
by